THE TRAGICOMIC REALISATION OF LIFE AND DESTINY OF KOCIC’S CHARACTERS - Soleša, Biljana S (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2017)
This paper discusses the collective identity of the characters of Kocic's prose. It examines the archetypal traits, oddify, originality and impressiveness of these unique characters in Serbian literature as well as the presence of collective memory, the awareness of one self and the others, historical, social and economic circumstances that surround Kocic’s heroes. Looking back at the elements of the creative process, the artist's motivation and the presence of the tragical and the comical can be singled out. The characters of Simeun Djak, David Strbac, Mracajski prota, Relja Knezevic have been analyzed, and a short review of the female characters is given. Revealing the extent to which the creativity of Petar Kocic coincides with the elements of history, psychology, sociology and anthropogeography, a literary-scientific thought on his work gets completed and the versality to approach to the reading is allowed.
Keywords: prose; hero; character; archetype; motivation